2016
DOI: 10.1007/s11906-015-0617-2
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A, Hypertension, and Cardiovascular Diseases: Epidemiological, Laboratory, and Clinical Trial Evidence

Abstract: Bisphenol A (BPA) exposure has become one of the most common environmental chemical exposures in humans. There is growing evidence regarding an association between BPA exposure, hypertension, and cardiovascular diseases (CVD). If BPA exposure is indeed associated with raised blood pressure and CVD, it would be a major public health problem. Therefore, we reviewed the epidemiological, laboratory, and clinical trial evidence for an association between BPA exposure, CVD, and hypertension, and discussed the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 44 publications
4
53
0
1
Order By: Relevance
“…This would suggest an avenue for homeostatic disruptions including cardiovascular effects and hypertension associated with BPA and, by extension, other EDCs (142, 143). Intriguingly, in humans, BPA exposure has been tentatively linked with cardiovascular disease and hypertension, but the causal mechanisms remain to be characterized (144). …”
Section: Avp Impacts—beyond Brain and Behaviormentioning
confidence: 99%
“…This would suggest an avenue for homeostatic disruptions including cardiovascular effects and hypertension associated with BPA and, by extension, other EDCs (142, 143). Intriguingly, in humans, BPA exposure has been tentatively linked with cardiovascular disease and hypertension, but the causal mechanisms remain to be characterized (144). …”
Section: Avp Impacts—beyond Brain and Behaviormentioning
confidence: 99%
“…Ponadto wykazano, iż substancja ta może powodować arytmię (43) oraz przyczyniać się do różnorodnych chorób serca, takich jak zawał mięśnia sercowego czy choroba niedokrwienna serca. Stwierdzono także, że ekspozycja na bisfenol A zwięk-sza ryzyko nadciśnienia i choroby wieńcowej (3,16,20). Pomimo stosunkowo znacznej liczby badań na temat negatywnego wpływu BPA na układ sercowo--naczyniowy (1,2,12,15,34), dokładny mechanizm tego działania nie został do końca poznany.…”
Section: Praca Oryginalnaunclassified
“…Moreover, it is known that BPA affects the liver, pancreas, and kidneys . Previous studies have shown that this toxin causes changes in the heart and blood vessels, which may lead to hypertension, heart attack, atherosclerosis, and stroke …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Previous studies have shown that this toxin causes changes in the heart and blood vessels, which may lead to hypertension, heart attack, atherosclerosis, and stroke. 20,21 Despite numerous studies on the influence of BPA on the living organisms, several aspects of the toxic properties of this substance remain unexplained, including the impact of this substance on the enteric nervous system (ENS). The ENS is the part of the autonomic nervous system, which is located in the wall of the GI tract and is characterized by significant independence from the brain.…”
mentioning
confidence: 99%